2020
DOI: 10.5115/acb.20.041
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal anatomy of the transverse sinus: implications for endovascular therapy

Abstract: Trabeculae or septations in the transverse sinus can have potentially life-threatening clinical significance. The current study demonstrates trabecula/septum patterning within the transverse sinus with measurements and distribution data supplemented by imaging, and describes the possible etiology of idiopathic intracranial hypertension and turbulent blood flow in the transverse sinus. Twenty-four sides from 12 cadaveric heads, all fresh-frozen, were used (five males, seven females; age at death 65-91 years, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Strydom et al [ 27 ] studied the transverse sinuses of both cadavers and patients and found that 29.4% of the 102 subjects had septations in them. Altafulla et al [ 28 ] also found a total of 42 septations in 24 cadaveric transverse sinuses studied (12 cadavers). In the present study, all basilar venous plexuses were found to contain such trabeculae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strydom et al [ 27 ] studied the transverse sinuses of both cadavers and patients and found that 29.4% of the 102 subjects had septations in them. Altafulla et al [ 28 ] also found a total of 42 septations in 24 cadaveric transverse sinuses studied (12 cadavers). In the present study, all basilar venous plexuses were found to contain such trabeculae.…”
Section: Discussionmentioning
confidence: 99%
“…Stenosis of the transverse sinus is also well known to contribute idiopathic intracranial hypertension [ 27 , 29 ]. The possible benefits of dural sinus septations were discussed by Altafulla et al [ 28 ] in their study of the architecture of transverse sinus trabeculations and their tensile strength. The authors suggested that these intraluminal septations help maintain the three-dimensional shape of the dural sinuses where hemodynamic stress was maximal, for instance where the direction of blood flow changes and in areas of maximum curvature of the sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…From an anatomical perspective, the TS is vulnerable to collapse toward the lateral side due to lack of supportive structures, such as the septum and trabecula. 18) In patients with IIH, sinus stenosis occurs in the lateral side of the TS; thus, SAS may occur in the remaining parts of TS after stenting for the same reason.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study, the mean diameter of the transverse sinus was 6.21 mm and 6.30 mm on right and left sides, respectively thus confirming it's variability. 22 The torcula which is the confluence of sinuses is believed to be located below or on the external occipital protuberance. However recent studies have shown that the torcula lies slightly superior or on the right side of the external occipital protuberance.…”
Section: Literature Reviewmentioning
confidence: 99%